Molecular footprints of human immunoglobulin gene evolution: a new sequence family. - Straubinger, B (1984)
Analysis of the human VK (ref. 2) gene locus led to the detection of a new sequence family (L sequences). Its copy number is in the range of 10(2). The L sequences, which are about 500 bp long, are found as part of the 3' flanking regions of a clustered set of human VKI genes but they occur also separate from the genes. Models are discussed in which L sequences are viewed as molecular footprints of amplification and transposition processes of VK genes.